Eco-Dyeing of Silk Fabric with Garcinia Dulcis (Roxb.) Kurz Bark as a Source of Natural Dye by using The Padding Technique. Issue 1 (2nd January 2016) - Mongkholrattanasit, Rattanaphol; Saiwan, Chintana; Rungruangkitkrai, Nattadon; Punrattanasin, Nattaya; Sriharuksa, Kamolkan; Klaichoi, Charoon; Nakpathom, Monthon
Abstract : Silk fabrics were put through a process of dyeing with natural colorants extracted and used from the bark of the Garcinia dulcis (Roxb.) Kurz. Two padding techniques, pad-batch and pad-dry, were used under different study conditions. The effects of mordant agents used on the fabrics and the natural colorant in the dyeing process, color values, color strength, and the fastness properties of silk fabric were investigated and the results recorded in the following study. The results showed that color values can be changed using various metallic salts as mordants. The fastness properties ranged from fair to very good, while perspiration and light fastness was poor to fair.